2022
DOI: 10.3389/frma.2022.950212
|View full text |Cite
|
Sign up to set email alerts
|

African researchers do not think differently about Open Data

Abstract: A key motivation for Open Science is accessibility. For researchers in resource-poor economies, this translates into access to the methods, data and publications that will foster scientific research and discovery in such communities and environments. Attitudes toward Open Science are in flux, and there is a growing awareness of the roles and responsibilities that researchers have to one another in this regard. This paper explores how African researchers approach issues relating to Open Data by reporting on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The demonstration of understanding and awareness of this concept is important as there is an increased demand placed on RECs to engage with protocols involving big data and AI-driven research that may need to be shared during collaborations [ 12 ]. Data sharing is an important part of open science as more institutions, journals, health research funders and governments emphasise the importance of open science and enforce open data policies intended to increase academic influences and promote scientific discovery and development for the greater benefit of the public [ 10 , 25 27 ]. Openness in science contributes to greater social impact on the public and our interviewees recognised its several benefits which are consistent with previous research [ 17 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of understanding and awareness of this concept is important as there is an increased demand placed on RECs to engage with protocols involving big data and AI-driven research that may need to be shared during collaborations [ 12 ]. Data sharing is an important part of open science as more institutions, journals, health research funders and governments emphasise the importance of open science and enforce open data policies intended to increase academic influences and promote scientific discovery and development for the greater benefit of the public [ 10 , 25 27 ]. Openness in science contributes to greater social impact on the public and our interviewees recognised its several benefits which are consistent with previous research [ 17 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Global South, which is a context where we have worked and conducted research, several challenges have limited researchers’ participation in open research practices at national and international levels. Whereas recent studies in Africa, for example, have shown that scholars are indeed ready to adopt open research practices such as data sharing, many researchers have seen open science as limiting because of multiple barriers such as inadequate research infrastructures, technology limitations, limited funding, lack of policy, high costs for open access publishing, and limited access to top‐ranked journals (Chiware & Skelly, 2022; Skelly & Chiware, 2022). Thus, the inequalities within global communities are being reflected in open science practices, and these inequalities are particularly damaging to researchers in the Global South.…”
mentioning
confidence: 99%
“…33 It is important that researchers and scientists are provided with the necessary resources and government support to reinforce their data-sharing processes. Furthermore, Skelly and Chiware 34 proposed that future policies define the roles of international research funders, journal publishers and inter-institutional and country collaborators to ensure equitable data custodianship in African-generated research. Data sharing is an important component of scientific investigation that should always strive to uphold the rights and interests of all stakeholders.…”
mentioning
confidence: 99%
“…Data sharing is an important component of scientific investigation that should always strive to uphold the rights and interests of all stakeholders. 34 This underscores the need for organisations and institutions to have data governance mechanisms in place, such as data management plans and policies that encapsulate ethical data-sharing practices. 35,36 Whilst the focus of this paper is not on big data from commercial endeavours, one must note that data regulations govern both commercial and non-commercial big data.…”
mentioning
confidence: 99%
See 1 more Smart Citation